Foraging benefits of winning intergroup encounters in colobus monkeys - Eva C. Wikberg; Sara Lucci; Emily Glotfelty; Fernando Campos; Pascale Sicotte (Primates, 2026)
Winners of aggressive intergroup encounters are often assumed to benefit from increased access to resources, but few studies have measured whether there is differential access to resources based on the intergroup outcome. To investigate whether winning intergroup encounters is associated with increased access to food, we used 13 months of data on intergroup dynamics, feeding by 61 females, and the phenology and spatial distributions of food trees from the home ranges of 8 groups of white-thighed black-and-white colobus ( Colobus vellerosus ) at Boabeng-Fiema, Ghana. Contested trees were important food species more often than expected based on the occurrence of these species in the study area. Contested trees had young leaves, fruits, and seeds more often than expected based on the presence of these plant parts on trees monitored via monthly phenology surveys. Focal females were more likely to feed on the contested tree than other trees they were in during and immediately after the intergroup encounter. Based on group scan data collected throughout the day of an intergroup encounter, the likelihood of females feeding on any food species before and during the intergroup encounter was similar regardless of the outcome. The likelihood of feeding was higher after the intergroup encounter if the group had won compared to if the group had lost. These findings indicate that groups compete over access to important food resources and winners benefit from increased access to food. Future studies should investigate whether winning intergroup encounters is associated with long-term benefits such as increased reproductive success.

MHC-DRB heterozygosity may increase subordinate but not alpha male siring success in white-faced capuchin monkeys (Cebus imitator) - Janet C. Buckner; Katharine M. Jack; Margaret Buehler; Amanda D. Melin; Valérie A. M. Schoof; Eva C. Wikberg; Saul Cheves Hernandez; Linda M. Fedigan; Jessica W. Lynch (Primates, 2026)

Social network dynamics, infant loss, and gut microbiota composition in female Colobus vellerosus during time periods with alpha male challenges - Shelby Samartino; Diana Christie; Anna Penna; Pascale Sicotte; Nelson Ting; Eva Wikberg (Primates, 2024)